1999
DOI: 10.1038/sj.bjc.6690816
|View full text |Cite
|
Sign up to set email alerts
|

Deletions at 14q in malignant mesothelioma detected by microsatellite marker analysis

Abstract: Summary Previous molecular cytogenetic studies by comparative genomic hybridization (CGH) on primary tumours of human malignant mesothelioma have revealed that loss of genetic material at chromosome 14q is one of the most frequently occurring aberrations. Here we further verify the frequency and pattern of deletions at 14q in mesothelioma. A high-resolution deletion mapping analysis of 23 microsatellite markers was performed on 18 primary mesothelioma tumours. Eight of these had previously been analysed by CGH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…As for potential TSGs, miR-34* and miR-429 are located at 1p36 while miR-203 resides at 14q32, which are all well documented to be frequently deleted (Tiainen et al, 1988;Kivipensas et al, 1996;Bjorkqvist et al, 1997;Krismann et al, 2002;Lindholm et al, 2007;Taniguchi et al, 2007). Loss of 14q is common in MM (Balsara et al, 1999;Bjorkqvist et al, 1999;De Rienzo et al, 2000) and as no target gene has yet been identified, one can speculate that miR-203 is that target. As a consequence of miR-203 deletion, its target gene JUN oncogene can carry on its oncogenetic properties without control.…”
Section: Discussionmentioning
confidence: 96%
“…As for potential TSGs, miR-34* and miR-429 are located at 1p36 while miR-203 resides at 14q32, which are all well documented to be frequently deleted (Tiainen et al, 1988;Kivipensas et al, 1996;Bjorkqvist et al, 1997;Krismann et al, 2002;Lindholm et al, 2007;Taniguchi et al, 2007). Loss of 14q is common in MM (Balsara et al, 1999;Bjorkqvist et al, 1999;De Rienzo et al, 2000) and as no target gene has yet been identified, one can speculate that miR-203 is that target. As a consequence of miR-203 deletion, its target gene JUN oncogene can carry on its oncogenetic properties without control.…”
Section: Discussionmentioning
confidence: 96%
“…Such obvious chromosomal imbalances favor the diagnosis of a benign or malignant neoplasm and argue against a reactive condition (15,16). In addition, loss of 6q and 22q, as well chromosomes 14 and 22 represent some of the most frequent and tumor-specific genetic imbalances in malignant mesothelioma (17)(18)(19)(20)(21), thus supporting cytologic diagnosis of malignancy (22). In contrast, loss of 22q is a very uncommon CGH finding in non-small-cell lung carcinomas (8,23), a tumor type, which must be distinguished from malignant mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been carried out using comparative genomic hybridization (CGH) to detect gene copy number alterations, i.e., losses, gains and amplifications. The most frequently reported aberrations by cytogenetic analyses or conventional CGH (cCGH) are losses at 1p21, 3p, 6q22, 9p21, 10pter ] p13, 13q, 14q, 17pter ] p12, and 22q, and gains at 1q23, 1q32, 3p21, 4p12 ] q13, 4q31 ] q32, 7p15 ] p14, 8q22 ] q23, and 15q22 ] q25 (Tiainen et al, 1989;Bjorkqvist et al, 1997Bjorkqvist et al, , 1998Bjorkqvist et al, , 1999Ascoli et al, 2001;Krismann et al, 2002). Because the resolution of cCGH is limited to chromosomal bands, a gene-level view cannot be obtained.…”
mentioning
confidence: 99%